Overweight, Obesity, and Neighborhood Characteristics among Postpartum Latinas - Colleen Keller; Michael Todd; Barbara Ainsworth; Kathryn Records; Sonia Vega-Lopez; Paska Permana; Dean Coonrod; Allison Nagle Williams (Journal of Obesity)
Background. Weight gain during the childbearing years and failure to lose pregnancy weight after birth contribute to the development of obesity in Latinas. Design and Methods. Madres para la Salud (Mothers for Health) is a 12-month prospective, randomized controlled trial exploring a social support intervention with moderate-intensity physical activity to effect changes in body fat, systemic and fat tissue inflammation, and depression symptoms in sedentary postpartum Latinas. This paper describes the initial body composition of the sample, social support, and neighborhood contextual correlations of overweight and obese Latina mothers within the first 6 months after birth. Results. The mean body mass index was 29.68 with 38.56% bioelectrical impedence analysis for body fat. Elements of the environment (e.g., opportunities to walk) received middle or high scores. Access to healthy food was positively related to favorability of the walking environment. Waist-to-hip ratio was uncorrelated with other obesity-related indices. Conclusions. The body adiposity of these Latina mothers was coupled with low levels of social support from family and friends and neighborhood characteristics that were unfavorable to walking.